Attitudes and beliefs about mental illness among church-based lay health workers: experience from a prevention of mother-to-child HIV transmission trial in Nigeria. Issue 1 (2nd January 2016) - Iheanacho, Theddeus; Kapadia, Daniel; Ezeanolue, Chinenye O.; Osuji, Alice A.; Ogidi, Amaka G.; Ike, Anulika; Patel, Dina; Stefanovics, Elina; Rosenheck, Robert; Obiefune, Michael; Ezeanolue, Echezona E.
Abstract : Common mental disorders are prevalent in Nigeria. Due to stigma and a limited number of trained specialists, only 10% of adults with mental illness in Nigeria receive any care. The Healthy Beginning Initiative is a community-based maternal/child health program that includes screening for perinatal depression and was implemented by lay, volunteer, church-based health advisors (CHAs). The aim of the study was to assess the beliefs and attitudes about mental illness among the CHAs. The study used a cross-sectional survey of 57 CHAs, who completed a 43-item, self-administered questionnaire that assessed their beliefs and attitudes about mental illness. The response rate was 71%. Respondents were mostly female (79%), married (83%) and aged 40–49 years ( M = 41.16 SD = 10.48). Most endorsed possession by evil spirits (84%), traumatic events (81%) and witchcraft (60%) as causes of mental illness. A majority (69%) believed that people with mental illness were a nuisance, and less than half (46%) believed that mental disorders were illnesses like any other illness. It is concluded that stigmatizing attitudes and beliefs about mental illness are common among the CHAs. Training for lay health workers in Nigeria should include education on the known bio-psycho-social basis of mental disorders and the role of social inclusion in recovery.